STUDIES ON SURFACE RADIO REFRACTIVITY OVER SOME SELECTED CITIES IN NORTH-CENTRAL, NIGERIA - Mmahi, Nnenna Okoro; Akinbolati, Akinsanmi; Ikechiamaka, Florence N.; Akpaneno, Francis A.; Joseph, Emmanuel; Ekundayo, Kehinde R (FUDMA JOURNAL OF SCIENCES, 2022)
This research investigated the variations of surface radio refractivity and its propagation effects on radio signal over the cities of Abuja and Ilorin, Nigeria. Six years (2015-2020) satellite data of Temperature, Pressure and Humidity both at the surface (12m) and at 100 m AGL, were used for the study. The data retrieved were used to determine the monthly, seasonal and annual surface radio refractivity values for the locations. Results show that the values of surface radio refractivity (Ns) in Abuja was slightly lower than Ilorin with average values of 335.62 and 351.07 N-Units obtained for the six years respectively. Average values of Ns, obtained during the dry season months in Abuja and Ilorin were 299.40 and 321.03(N-units) respectively while average values of 360.24 and 368.21 (N-units) were obtained during the wet season months in Abuja and Ilorin respectively. Higher values of Ns, were recorded generally during wet compared to the dry seasons’ months in all the years and study locations. The implication of this is higher attenuation of radio signal due to Ns during wet compared to the dry seasons’ months and as well as in Ilorin compared to Abuja. Correlation coefficients of -0.53, 0.98 and 0.53 were determined between (Ns) and; temperature, humidity and pressure respectively in Abuja while -0.30, 0.97 and 0.34 were determined between Ns and; temperature, humidity and pressure respectively in Ilorin. The overall findings of this work will be useful to radio engineers for the proper planning of reliable power budget over the study areas.